Kinematic adaptations in sprint acceleration performances without and with the constraint of holding a field hockey stick - Wdowski, M. M.; Gittoes, M. J. R. (Sports Biomechanics, 2013)
The aim of this study was to investigate the technique adaptations made when performing sprint-based tasks without (free condition) and with (constrained condition) the constraints of carrying a field hockey stick. Three free and three constrained maximal sprint accelerations were performed by 18 experienced university male field hockey players (age = 20 ± 1 years, body mass = 73.3 ± 7.1 kg, and stature = 1.78 ± 0.05 m). An automatic motion analysis system tracked sagittal plane active marker locations (200 Hz). M sprint velocity during the 18-22 m (free: 8.03 ± 0.43 m/s; constrained: 7.93 ± 0.36 m/s) interval was significantly (p = 0.03) different between free and constrained conditions. While the M stride length and stride frequency was similar between free and constrained conditions in the 2-13 m capture volume, the free condition elicited a 0.10 m/s faster (p = 0.03) stride velocity. Further significant differences were found between free and constrained kinematic profiles (p <= 0.05) for the hip angular velocity at touchdown during the 2-12 m interval of the sprints and in the overall sprint technique coordination between free and constrained conditions. Performance and technique adaptations indicated that sprint-training protocols for field sports should integrate specific equipment constraints to ensure explicit replication of the mechanical demands of the skills underpinning superior performance.